Researching several problems of EMU CCE/ERM based on VxWorks 6.x - Zhou Haoshang; Gao Zhaoling (Dianzi Jishu Yingyong, 2025)
In the network communication control system of rail transit, in order to ensure the stability of vehicle control and the accuracy and reliability of operation data and fault records, the central control unit (CCU) and event record machine (ERM), the key components, adopt an embedded real-time operating system VxWorks. Generally, when the system starts, it needs to start the DOS first, and then it is started as a general software call. In this paper, based on the system startup failure and the failure of 6 lights on the front panel, it studies the influence of DOS reading and writing to the electronic disk on its startup process, and proposes and validates a solution that can directly start on the FAT32 format electronic disk to avoid the problem of system startup failure. Then, according to the problems of UDP unicast, FTP file transfer, DBR startup check and LBA sector read and write in different versions of VxWorks encountered by the author, the solutions are put forward.